Classification Of Educational Excellence The Child With Special Needed - Syarif, Muhammad Syarif; Eka Mayasari; Chairullah (ASIAN PUBLISHER, 2024)
Exceptional children are children who require special needs and treatment because of developmental disorders and abnormalities they experience. Children with special needs have differences that occur in several ways, such as the process of growth and development that experiences abnormalities or deviations both physically, mentally, intellectually, socially and emotionally. This research uses qualitative research which is library research. Secondary data sources from this study are journals and literature that can support the analysis or relate to the discussion. The results of the study show that children with special needs are children with specificities and needs that are different from other normal children. These different specialties include physical, mental, intellectual, social or emotional specialties. So that each specialty requires a different handler. The classification of children with special needs includes blind, deaf, disabled, mute, autism, mentally retarded, mentally retarded and gifted children. Children with their respective specialties certainly need assistance to realize their potential into real achievements with special services.